2002
DOI: 10.1210/endo.143.5.8767
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Thyroid Hormones and 3,5-Diiodothyronine on Membrane Transport Systems in Chick Embryo Hepatocytes

Abstract: Rapid nongenomic effects of thyroid hormones L-T(3) and L-T(4) on two plasma membrane transport systems were investigated in 14-d-old and 19-d-old chick embryo hepatocytes. The Na(+)/H(+) exchanger activity was measured using the intracellular pH-sensitive fluorescent probe 2',7'-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein acetoxymethyl ester, whereas the amino acid transport was estimated by [1-(14)C]-2-aminoisobutyric acid uptake. System A amino acid transport activation was linear to hormone concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Recently, Incerpi et al (11) reported that T3 stimulated Na ϩ /H ϩ exchanger in chick embryo hepatocytes. This effect was sensitive to PI3K inhibitor wortmannin (50 nM), but direct activation of PI3K by T3 was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Incerpi et al (11) reported that T3 stimulated Na ϩ /H ϩ exchanger in chick embryo hepatocytes. This effect was sensitive to PI3K inhibitor wortmannin (50 nM), but direct activation of PI3K by T3 was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone (T4) recently was reported to activate the mitogen-activated protein kinase in HeLa and CV-1 cells (10). The T3-induced activity of Na ϩ /H ϩ exchanger and system A amino acid transport in chick embryo hepatocytes was blocked by inhibitors of protein kinase C and PI3K (11). Thyroid hormone differentially regulates Na,K-ATPase isoforms in both tissue-and cell type-specific manners (1).…”
mentioning
confidence: 99%
“…Intracellular action of T 2 also is described in avian cells during fetal development and cell differentiation (Incerpi et al 2002). T 2 regulates DNA synthesis, cell-cycle proteins (Alisi et al 2004), and several membrane-associated transport systems, whose activity is related to cell proliferation (Incerpi et al 2002(Incerpi et al , 2005.…”
Section: 5-diiodo-l-thyroninementioning
confidence: 99%
“…T 2 regulates DNA synthesis, cell-cycle proteins (Alisi et al 2004), and several membrane-associated transport systems, whose activity is related to cell proliferation (Incerpi et al 2002(Incerpi et al , 2005. T 2 's effect on the Na C -H C exchanger was identified for 14-day-and 19-dayold cells, whereas the effect on amino acid transport was present at late stages of embryo development.…”
Section: 5-diiodo-l-thyroninementioning
confidence: 99%
See 1 more Smart Citation